Do helminth infections underpin urban‐rural differences in risk factors for allergy‐related outcomes?. Issue 5 (25th January 2019) - Nkurunungi, Gyaviira; Lubyayi, Lawrence; Versteeg, Serge A.; Sanya, Richard E.; Nassuuna, Jacent; Kabagenyi, Joyce; Kabuubi, Prossy N.; Tumusiime, Josephine; Zziwa, Christopher; Kizindo, Robert; Niwagaba, Emmanuel; Nanyunja, Carol; et al.
Summary: Background: It is proposed that helminth exposure protects against allergy‐related disease, by mechanisms that include disconnecting risk factors (such as atopy) from effector responses. Objective: We aimed to assess how helminth exposure influences rural‐urban differences in risk factors for allergy‐related outcomes in tropical low‐ and middle‐income countries. Methods: In cross‐sectional surveys in Ugandan rural Schistosoma mansoni ( Sm )‐endemic islands, and in nearby mainland urban communities with lower helminth exposure, we assessed risk factors for atopy (allergen‐specific skin prick test [SPT] reactivity and IgE [asIgE] sensitization) and clinical allergy‐related outcomes (wheeze, urticaria, rhinitis and visible flexural dermatitis), and effect modification by Sm exposure. Results: Dermatitis and SPT reactivity were more prevalent among urban participants, urticaria and asIgE sensitization among rural participants. Pairwise associations between clinical outcomes, and between atopy and clinical outcomes, were stronger in the urban survey. In the rural survey, SPT positivity was inversely associated with bathing in lakewater, Schistosoma‐ specific IgG4 and Sm infection. In the urban survey, SPT positivity was positively associated with age, non‐Ugandan maternal tribe, being born in a city/town, BCG scar and light Sm infection. Setting (rural vs urban) was an effect modifier for risk factors including Sm‐ and Schistosoma‐ specific IgG4. In both surveys, the dominant risk factors for asIgE sensitization were Schistosoma ‐specific antibody levels and helminth infections. Handwashing and recent malaria treatment reduced odds of asIgE sensitization among rural but not urban participants. Risk factors for clinical outcomes also differed by setting. Despite suggestive trends, we did not find sufficient evidence to conclude that helminth ( Sm ) exposure explained rural‐urban differences in risk factors. Conclusions and clinical relevance: Risk factors for allergy‐related outcomes differ between rural and urban communities in Uganda but helminth exposure is unlikely to be the sole mechanism of the observed effect modification between the two settings. Other environmental exposures may contribute significantly.